Analisis Deklarasi Universal Hak Asasi Manusia (DUHAM) Terhadap Kelompok Minoritas Transgender di Kota Tasikmalaya - Isti Azhari Putri Suntian (Epistemik: Indonesian Journal of Social and Political Science, 2023)
In this manuscript the author will discuss about discrimination behaviour that are left by the transgender group in Tasikmalaya. This research shows how transgender group in Tasikmalaya get some discrimination by many people in Tasikmalaya and also how the state can protect to their human rights. This study will be more in-depth to discuss how the reality of freedom is written in the UDHR, especially article 2 against the Transgender minority group in the city of Tasikmalaya, and how people who are part of the Transgender carry out their social life with the community. Theories used in this research are the theory of Democracy and Human Rights and phenomenological approach with descriptive qualitative research method. The result of this research there are three discriminatory behaviors are felt by the Transgender group in Tasikmalaya, the first is the availability of housing, religion, and education. The state in its efforts to protect the human rights of its citizens then mobilized related agencies together with PKBI and KPA in guiding transgender groups in Tasikmalaya to be able to develop in a more positive direction. Through the network created by the transgender community of Tasikmalaya together with PKBI and other related agencies, so as transgender minority group in Tasikmalaya have begun to not get discrimination with the help of PKBI, KPA, and relevant agencies.